Renal function and urological complications after radical hysterectomy with postoperative radiotherapy and platinum-based chemotherapy for cervical cancer. (10th November 2017) - Okadome, Masao; Saito, Toshiaki; Kitade, Shoko; Ariyoshi, Kazuya; Shimamoto, Kumi; Kawano, Hiroyuki; Minami, Kazuhito; Nakamura, Motonobu; Shimokawa, Mototsugu; Okushima, Kazuhiro; Kubo, Yuichiro; Kunitake, Naonobu
Abstract : Platinum-based chemotherapy to treat cervical cancer poses a risk of causing renal dysfunction. Postoperative radiotherapy caused bladder wall thickening, resulting in urological complications. The life-threatening complication rate was 0.6%. Abstract: Background: We aimed to clarify renal functional changes long term and serious urological complications in women with cervical cancer who undergo radical hysterectomy followed by pelvic radiotherapy and/or platinum-based chemotherapy to treat the initial disease. Methods: Data on 380 women who underwent radical hysterectomy at the National Kyushu Cancer Center from January 1997 to December 2013 were reviewed. Main outcome measures were the estimated glomerular filtration rate (eGFR) and monitored abnormal urological findings. Results: Postoperative eGFR was significantly lower than preoperative eGFR in 179 women with surgery alone and in 201 women with additional pelvic radiotherapy and/or chemotherapy (both P < 0.01). Two types of univariate analyses for eGFR reduction in women after treatment showed that older age, advanced stage, pelvic radiotherapy, and platinum-based chemotherapy were significant variables on both analyses. Two types of multivariate analyses showed that platinum-based chemotherapy or pelvic radiotherapy were associated with impaired renal function (odds ratio 1.96, 95% confidence interval 1.08–3.54 and odds ratio 2.85, 95% confidence interval 1.12–7.24, for the respective analyses). There was a higher rate of bladder wall thickening in women with pelvic radiotherapy had than those without it (17.4% vs. 2.7%, P < 0.01). One serious urological complication (intraperitoneal rupture of the bladder) occurred among women who underwent pelvic radiotherapy (0.6% vs. 0%). Conclusions: Surgeons should be aware that eGFR is reduced after platinum-based chemotherapy and/or postoperative pelvic radiotherapy. Serious and life-threatening urological complications are rare, but surgeons should be aware of the possibility during the long follow-up.